Book Review. Richard Walsh (ed.), T&T Clark Companion to the Bible and Film Journal for Religion, Film and Media - Daria Pezzoli-Olgiati (Journal for Religion, Film and Media, 2020)
"The strength of the Bible lies in the fact that it is a good screenplay," said Godard once. The T&T Clark Companion to the Bible and Film edited by Richard Walsh demonstrates that Godard was absolutely right. The book is a treasure trove that can be used as an introduction to research in this field and for teaching on the academic level.